Pengaruh Model Pembelajaran dan Gaya Kognitif Terhadap Hasil Belajar Sejarah Siswa di SMAN 28 Kab. Tangerang - Mirla Safrina boru (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2017)
The research aim to investigate the influence of instructional models cognitive style toward history learning outcome of students at SMA Negeri 28 Kab. Tangerang. This research is quantitative research using design treatment by level 2x2. The population of this research is all students of X IIS grade. The sample consist of two classes that X IIS 2 and X IIS 4 with 67 people amount. For the experimental class X IIS 2 are 32 student and from control class X IIS 4 are 35 student will be selected. The instrument used to assess students achievement is in the multiple choice form, while the instrument used to assess students cognitive style is in test GEFT. Among the result of the research are: (1) History learning outcome of students who follow TGT instructional models higher than the student who studied with direct instruction model, (2) History learning outcome of students who have Field Independent cognitive style higher than student who have a Field Dependent cognitive style, (3) There is interaction effect between models of instructional and cognitive style on history learning outcome of student.